FATIGUE LIFE OF TUBULAR PROFILE ALUMINUM ALLOY 6013-T6 - Cornelis Voorwald, Herman Jacobus [UNESP] (2016)
The fork suspension's steerer tube in a bicycle is a component of great importance considering that dynamic loading during operation may cause accident to the rider. This component is manufactured by machining processes from aluminum alloy 6013-T6 extrusion tubular profile. The objective of the present paper is to study the effect of different shot peening conditions on the fatigue behavior of the material and, as a consequence, increases in the useful life/safety of the structure. Experimental results showed that thread forming by manufacturing process increased the fatigue strength of the aluminum alloy, in comparison to the manufacturing process through conventional machining.